Koncept "religiâ" v dumovij kartini svitu - Mihno, Lûdmila (Stylistyka, 2010)
The article deals with the concept of “religion” in the Ukrainian folklore. Linguistic umts in which the concept of religion appears are presented. The author analyses lexical and phraseological materiał which forms the kemel of this concept. The research results confirm the idea of the dumas language connect-m with the religious source.